Stage III and oestrogen receptor negativity are associated with poor prognosis after adjuvant high-dose therapy in high-risk breast cancer - Hohaus, Stefan; Funk, Liane; Martin, Simona; Schlenk, Richard Friedrich; Abdallah Khalafallah, Alhossain; Hahn, Uwe; Egerer, Gerlinde; Goldschmidt, Hartmut; Schneeweiss, Andreas; Fersis, Nikolaos Erich; Kaul, Sepp; Wallwiener, Diethelm; et al. (British journal of cancer, 1999)
We report on the efficacy and toxicity of a sequential high-dose therapy with peripheral blood stem cell (PBSC) support in 85 patients with high-risk stage II/III breast cancer. There were 71 patients with more than nine tumour-positive axillary lymph nodes. An induction therapy of two cycles of ifosfamide (total dose, 7.5 g m-2) and epirubicin (120 mg m-2) was given, and PBSC were harvested during G-CSF-supported leucocyte recovery following the second cycle. The PBSC-supported high-dose chemotherapy consisted of two cycles of ifosfamide (total dose, 12 000 mg m-2), carboplatin (900 mg m-2) and epirubicin (180 mg m-2). Patients were autografted with a median number of 3.7 × 106 CD34+ cells kg-1 (range, 1.9-26.5 × 106) resulting in haematological reconstitution within approximately 2 weeks following high-dose therapy. The toxicity was moderate in general, and there was no treatment-related toxic death. Twenty-one patients relapsed between 3 and 30 months following the last cycle of high-dose therapy (median, 11 months). The probability of disease-free and overall survival at 4 years were 60% and 83%, respectively. According to a multivariate analysis, patients with stage II disease had a significantly better probability of disease-free survival (74%) in comparison to patients with stage III disease (36%). The probability of disease-free survival was also significantly better for patients with oestrogen receptor-positive tumours (70%) compared to patients with receptor-negative ones (40%). Bone marrow samples collected from 52 patients after high-dose therapy were examined to evaluate the prognostic relevance of isolated tumour cells. The proportion of patients presenting with tumour cell-positive samples did not change in comparison to that observed before high-dose therapy (65% vs 71%), but a decrease in the incidence and concentration of tumour cells was observed over time after high-dose therapy. This finding was true for patients with relapse and for those in remission, which argues against a prognostic significance of isolated tumour cells in bone marrow. In conclusion, sequential high-dose chemotherapy with PBSC support can be safely administered to patients with high-risk stage II/III breast cancer. Further intensification of the therapy, including the addition of non-cross resistant drugs or immunological approaches such as the use of antibodies against HER-2/NEU, may be envisaged for patients with stage III disease and hormone receptor-negative tumours.